In Vitro Anti-Listerial Activities of Crude n-Hexane and Aqueous Extracts of Garcinia kola (heckel) Seeds - Penduka, Dambudzo (Molecular Diversity Preservation International (MDPI), 2011)
We assessed the anti-Listerial activities of crude n-hexane and aqueous extracts of Garcinia kola seeds against a panel of 42 Listeria isolates previously isolated from wastewater effluents in the Eastern Cape Province of South Africa and belonging to Listeria monocytogenes, Listeria grayi and Listeria ivanovii species. The n-hexane fraction was active against 45% of the test bacteria with zones of inhibition ranging between 8–17 mm, while the aqueous fraction was active against 29% with zones of inhibition ranging between 8–11 mm. The minimum inhibitory concentrations (MIC) were within the ranges of 0.079–0.625 mg/mL for the n-hexane extract and 10 to >10 mg/mL for the aqueous extract. The rate of kill experiment carried out for the n-hexane extract only, revealed complete elimination of the initial bacterial population for L. grayi (LAL 15) at 3× and 4× MIC after 90 and 60 min; L. monocytogenes (LAL 8) at 3× and 4× MIC after 60 and 15 min; L. ivanovii (LEL 18) at 3× and 4× MIC after 120 and 15 min; L. ivanovii (LEL 30) at 2, 3 and 4× MIC values after 105, 90 and 15 min exposure time respectively. The rate of kill activities were time- and concentration-dependant and the extract proved to be bactericidal as it achieved a more than 3log(10) decrease in viable cell counts after 2 h exposure time for all of the four test organisms at 3× and 4× MIC values. The results therefore show the potential presence of anti-Listerial compounds in Garcinia kola seeds that can be exploited in effective anti-Listerial chemotherapy.